Pengelolaan Drainase Kota Sebagai Upaya Mitigasi Banjir Kota Makassar - Ibrahim Djamaluddin; Sumarni Hamid Aly; Irwan Ridwan Rahim; Achmad Zubair; Rosalinda Ibrahim; Nurjannah Oktorina Abdullah (Faculty of Engineering UNHAS, 2020)
Floods in Makassar City are influenced by two main factors, namely: natural factors such as rainfall and topography, and human factors with all their activities that can affect the drainage system and the state of land cover. Most of the water drainage system in Makassar City only relies on the drainage network from small channels to large channels such as canals which are generally flowed by gravity into the sea, so that areas that have undergone a change in land cover function that were previously water infiltration into urban areas are very easy to floods because water drains cannot run properly resulting in frequent flooding, especially in areas that have low ground levels. Aquapond is a retention pond system that is widely used in Japan which functions as a temporary storage of rainwater when rainfall is high and drains it slowly after the rainfall subsides as a solution to urban water drainage management techniques which often experience overflow of water or flooding. Japanese technology retention ponds such as Aquapond were piloted in one place that often experiences flooding every year in Makassar City, namely Jalan Urip Sumohardjo in front of the South Sulawesi governor's office which is expected to be useful in managing the water drainage system which often overflows and causes flooding that disrupts traffic of road. Because the retention pond system is connected to water drainage channels, this water management method is not widely understood by the general public and the local government, so learning and outreach activities regarding planning and design, construction as well as operation and maintenance of Aquapond retention ponds are carried out. The process of implementing this service activity has involved the community, local government and Japanese experts both in the learning process in planning and design, reviewing Aquapond construction.